The effects of flavonoid supplementation on the mental health of postpartum parents - Colombage, Rebecca Logan; Holden, Sean; Lamport, Daniel Joseph; Barfoot, Katie Louise (Frontiers in Global Women's Health, 2024)
Introduction During the postpartum period, parents face psychological challenges and consequently, changes in mood and associated mood disorders have become increasingly prevalent in the 6-months following birth. Dietary flavonoids have been found to benefit mood and are therefore an appealing non-pharmacological option for potentially treating mood disorders in the postpartum. The aim of this study was to investigate whether a two-week dietary flavonoid intervention would improve mothers’ and fathers’ mental health in the immediate 6-month postpartum period. Method The study employed a randomised, parallel groups, controlled design to explore the effects of a flavonoid intervention vs. control group on several outcomes, including mood (PANAS), postpartum depression (EPDS), postpartum anxiety (PSAS-RSF-C) and quality of life (WHOQOL). Sixty participants (mothers n = 40, fathers n = 20) in the 6-month post-partum period were randomised to either a “flavonoid” or “control” condition. The flavonoid group were asked to add two flavonoid-rich foods (approximate flavonoid intake 218 mg/day) into their daily diet whilst controls (n = 23) were asked to continue with their usual diet for two-weeks (ClinicalTrials.gov (NCT04990622). Results Significant effects were found in the flavonoid group where mothers reported higher positive affect and lower postpartum depression after the two-week intervention relative to baseline. This finding is especially relevant as a clinical reduction in postpartum depression scores in the flavonoid group by an average 2.6 scoring points was observed, which equated to a reduction from “possible depression” at baseline to “little or no depression” at 2-weeks, which was not observed in the control group. Fathers’ data was not analysed due to non-compliance with the intervention. Discussion This study provides evidence for the benefits of a dietary flavonoid intervention for mood and mental health in new mothers, supporting the utility of non-pharmacological, self—administrable changes to the diet for improving positive mood outcomes and reducing symptoms of postpartum depression in mothers during an especially challenging time. Further research for the effect of dietary interventions on paternal mental health is needed. Clinical Trial Registration ClinicalTrials.gov, identifier NCT04990622.